Lead optimisation of an indole based HIV-1 non-nucleoside reverse transcriptase inhibitor - Brigg, Siobhan Ernan (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.